Human Resource Development for Sustainable Construction, Disasters Risk Reduction and Climate Change Adaptation - Shrestha, Diwat Kumar; Praveen, B. M. (International Journal of Atharva, 2025)
Human Resource Development (HRD) plays a critical role in achieving sustainable construction, disaster risk reduction (DRR), and climate change adaptation (CCA) in Nepal. As a country highly vulnerable to earthquakes, landslides, and climate-induced hazards, Nepal requires a skilled workforce capable of developing resilient infrastructure, implementing disaster preparedness strategies, and adopting climate-adaptive solutions. This article explores the current status, challenges, and future directions of HRD in these sectors, emphasizing technical and vocational training (TVET), policy and institutional frameworks, capacity-building programs, and community-based skill development. Despite policy advancements, including the National Building Code (NBC, 2020), National Adaptation Plan (NAP), and Technical and Vocational Education and Training (TVET) programs, significant gaps remain in implementation, institutional coordination, and equitable access to training opportunities. Key challenges include limited skilled workforce, weak enforcement of construction standards, insufficient funding, and lack of climate-responsive education. Additionally, rural and marginalized communities often have limited access to HRD opportunities, further exacerbating vulnerabilities. To address these gaps, Nepal must adopt strategic HRD interventions, such as integrating DRR and CCA into education, expanding technical training in sustainable infrastructure, strengthening policy implementation, and leveraging digital technologies for capacity-building. Moreover, public-private partnerships, research on climate-resilient materials, and inclusive skill development programs will be essential in building a competent workforce capable of driving sustainable development and disaster resilience. By prioritizing HRD as a key enabler, Nepal can foster a skilled, adaptive, and resilient workforce that contributes to a sustainable and disaster-resilient future.